Application of Think Talk Write (Ttw) Learning Model Based on Padlet Media on Students' Writing Skills at Madrasah Aliyah Paradigma Palembang - Petricia, Aisyah; Machmudah, Umi; Yurisa, Penny Respati (Abjadia : International Journal of Education, 2025)
The application of learning models and media that are less varied causes boredom and makes students less interested in learning. In this case, the researcher examines the application of the Think Talk Write (TTW) learning model based on Padlet media as an alternative for maharah kitabah learning. The purpose of this study was to determine whether the application of the Think Talk Write (TTW) model can increase students' interest and motivation in learning the Arabic maharah kitabah subject and how students respond when the Think Talk Write model based on Padlet media is applied to maharah kitabah learning. The type of research used is pre-experimental designs research with a one shot case study design. It is said to be pre-experimental because this design is not yet a real experiment. This study involved one class, namely the experimental class, which used the think Talk Write (TTW) model based on Padlet media in learning Arabic. The research sample consisted of 25 students. Data collection was carried out by observation, interviews, questionnaires and documentation. The instruments used in the study were pre-test and post-test. The results of the study showed that there was an increase in student interest and motivation as evidenced by the pre-test and post-test scores in the experimental class, where the pre-test score was 47.57 and the post-test score was 85.62. In addition, it was proven by the results of the t-test which showed that the significance value was less than 0.005 so that it can be stated that there is an influence of the Think Talk Write (TTW) model based on Padlet media on Arabic language learning materials, especially on the Maharah Kitabah.